Development of Clinical Guideline of Blood Transfusion Process in Children with Thalassemia - Sedigheh Khanjari; Razieh Talebi; Seyedeh Fatemeh Haghdoost Oskouie (Tehran University of Medical Sciences, 2015)
Background & Aim: The &beta-Thalassemia major is a chronic disease that needs a regular blood transfusion. The blood transfusion is a complex process with high probability of human errors during the process which results in serious adverse events in patients. Nurses should deliver care based on the best available evidence or best practice. The aim of this study was to develop an evidence-based clinical guideline of blood transfusion in children with thalassemia .   Methods & Materials: This study was conducted during 16 months from 2013 to 2014 based on three-step process of guideline adaptation including set up, adaptation and finalization. During these steps, topic and aims of the study were clearly identified. Then health questions were designed based on the PIPOH method. After conducting systematic searches, quality of the retrieved clinical guidelines was evaluated using the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument and a committee consisting of experts and policy-makers in nursing field. After external review, expert panel meetings and consensus between members, the final version of the guideline was developed .    Results: The criteria of clinical practice regarding stages of blood transfusion were determined based on the evidence, cultural and health conditions and were presented in twelve sections.   Conclusion: This clinical practice guideline developed based on evidence can guide blood transfusion process in clinical practice.